Analysis and multi-objective optimal design of a planar differentially driven cable parallel robot. Issue 12 (4th December 2021) - Wang, Ruobing; Li, Yangmin
Abstract: In this work, a planar cable parallel robot (CPR) driven by four cable-and-pulley differentials is proposed and analyzed. A new cable-and-pulley differential is designed by adding an extra pulley to eliminate the modeling inaccuracies due to the pulley radius and obviate the need of solving the complex model which considers the pulley kinematics. The design parameters of the proposed CPR are determined through multi-objective optimal design for the largest total orientation wrench closure workspace (TOWCW) and the highest global stiffness magnitude index. The proposed differentially driven CPR is evaluated by comparing various performance indices with a fully actuated CPR.